Analysis of the main aspects of testing laboratories in Turkey - Gumenyuk, Galina; Silonova, Natalia; Sen, Natalia (My University, 2017)
The achievement of quality management system in test laboratories will be the development, based on the results of theoretical and practical studies, of regulatory documents, statistics, accreditation body guidelines, quality manuals and laboratory procedures, common criteria for assessing the extent to which quality management systems of testing laboratories meet the requirements of international standards.
Keywords: laboratories; лабораторії; Turkey; Туреччина; кафедра експертизи харчових продуктів; якість сировини